Reciprocal Regulation Between Smad7 and Sirt1 in the Gut - Sedda, Silvia; Franzè, Eleonora; Bevivino, Gerolamo; Di Giovangiulio, Martina; Rizzo, Angelamaria; Colantoni, Alfredo; Ortenzi, Angela; Grasso, Enrico; Giannelli, Mario; Sica, Giuseppe S.; Fantini, Massimo Claudio; Monteleone, Giovanni (Frontiers in Immunology, 2018)
In inflammatory bowel disease (IBD) mucosa, there is over-expression of Smad7, an intracellular inhibitor of the suppressive cytokine TGF-β1, due to post-transcriptional mechanisms that enhance Smad7 acetylation status thus preventing ubiquitination-mediated proteosomal degradation of the protein. IBD-related inflammation is also marked by defective expression of Sirt1, a class III NAD+-dependent deacetylase, which promotes ubiquitination-mediated proteosomal degradation of various intracellular proteins and triggers anti-inflammatory signals. The aim of our study was to determine whether, in IBD, there is a reciprocal regulation between Smad7 and Sirt1. Smad7 and Sirt1 were examined in mucosal samples of IBD patients and normal controls by Western blotting and immunohistochemistry, and Sirt1 activity was assessed by a fluorimetric assay. To determine whether Smad7 is regulated by Sirt1, normal or IBD lamina propria mononuclear cells (LPMC) were cultured with either Sirt1 inhibitor (Ex527) or activator (Cay10591), respectively. To determine whether Smad7 controls Sirt1 expression, ex vivo organ cultures of IBD mucosal explants were treated with Smad7 sense or antisense oligonucleotide. Moreover, Sirt1 expression was evaluated in LPMC isolated from Smad7-transgenic mice given dextran sulfate sodium (DSS). Up-regulation of Smad7 was seen in both the epithelial and lamina propria compartments of IBD patients and this associated with reduced expression and activity of Sirt1. Activation of Sirt1 in IBD LPMC with Cay10591 reduced acetylation and enhanced ubiquitination-driven proteasomal-mediated degradation of Smad7, while inhibition of Sirt1 activation in normal LPMC with Ex527 increased Smad7 expression. Knockdown of Smad7 in IBD mucosal explants enhanced Sirt1 expression, thus suggesting a negative effect of Smad7 on Sirt1 induction. Consistently, mucosal T cells of Smad7-transgenic mice contained reduced levels of Sirt1, a defect that was amplified by induction of DSS-colitis. The data suggest the existence of a reciprocal regulatory mechanism between Smad7 and Sirt1, which could contribute to amplify inflammatory signals in the gut.